2018
DOI: 10.3390/f9110728
|View full text |Cite
|
Sign up to set email alerts
|

Megaspore Chromosome Doubling in Eucalyptus urophylla S.T. Blake Induced by Colchicine Treatment to Produce Triploids

Abstract: Triploids generally provide an advantage in vegetative growth in forest trees. However, the technique of triploid breeding is still an open field in the Eucalyptus tree species. This study aims to explore the colchicine treatment technique for megaspore chromosome doubling to establish triploids in this tree species. Cytological observation on microsporogenesis and megasporogenesis was carried out to guide megaspore chromosome doubling induced by colchicine treatment. Ploidy level in progenies was detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The results suggested that stomata in tetraploid plants were larger but fewer (in area unit of leaf) compared to the control plants. These results are consistent with other studies (6,8,17,24,34,35,40). The increased cell size as exemplified by enlarged stomata size in triploid may play an important role in increasing the size of the leaves, which was also observed in this study.…”
Section: Effects Of Ploidy Level On Stomata Charactersupporting
confidence: 94%
See 1 more Smart Citation
“…The results suggested that stomata in tetraploid plants were larger but fewer (in area unit of leaf) compared to the control plants. These results are consistent with other studies (6,8,17,24,34,35,40). The increased cell size as exemplified by enlarged stomata size in triploid may play an important role in increasing the size of the leaves, which was also observed in this study.…”
Section: Effects Of Ploidy Level On Stomata Charactersupporting
confidence: 94%
“…Roy et al, (29) was suggested that the length and diameter of the stomata were set to be standard parameters for identification of tetraploid plants. Other reports on stomata size in the guard cells indicated that these cells are more dependent on genetic than environmental factors as compared to other cells in plant (40). The results suggested that stomata in tetraploid plants were larger but fewer (in area unit of leaf) compared to the control plants.…”
Section: Effects Of Ploidy Level On Stomata Charactermentioning
confidence: 81%
“…It inhibits microtubule polymerization by binding to tubulin, and thus it inhibits the mitotic spindle formation resulting in the development of a polyploid cell. Colchicine has been successfully used to induce 2n female gametes by treating embryo sacs, zygotes, and somatic cells, furthermore, a large number of triploids and tetraploids have been generated in Populus (Li et al, 2001;Kang et al, 2004;Wang et al, 2010a,b;Cai and Kang, 2011;Xu et al, 2016), Robinia pseudoacacia (Ewald et al, 2009), Eucommia ulmoides (Zhang et al, 2008), and Eucalyptus urophylla (Yang et al, 2018). Colchicine has also been applied to induce 2n pollen production in Populus (Li et al, 2014;Zhao et al, 2017Zhao et al, , 2019, Eucommia ulmoides , and Eucalyptus (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, polyploids have been widely used in fruit tree production [4][5][6]. The use of colchicine [7,8] or high temperature [9,10] to induce the formation of 2n gametes and their use in controlled pollinations is an important approach to obtain triploid progeny [11]. As a polyploidization agent, colchicine treatment is the most common and effective method applied to produce diploid gametes and triploids, as has been reported for poplar [12], cassava [13], Eucalyptus [14], and Cymbidium [15].…”
Section: Introductionmentioning
confidence: 99%
“…During fertilization, the induced 2n pollen usually exhibits weaker development and competitiveness compared with haploid pollen [18], whereas 2n female gametes show greater efficiency for formation of triploids by hybridization [19]. Induction of 2n female gametes by chromosome doubling in the megaspore or embryo sac has been Forests 2021, 12, 112 2 of 16 successfully used to obtain triploid plants in poplar [20], mulberry [21], Eucalyptus [8], Eucommia [9]. However, few studies have investigated artificial induction of unreduced gametes to induce polyploidy in fruit trees.…”
Section: Introductionmentioning
confidence: 99%